Recent advances in the black hole information problem - Rocha, J. V. (Webinar @ Sapienza Università di Roma, 2021)
For nearly 50 years, general relativists have been vexed by the celebrated black hole information paradox. This is a deep conceptual problem arising from conflicting conclusions reached by two distinct lines of thought, both of which are rooted in essential tenets of physics: the validity of semiclassical gravity in low-energy regimes, on the one hand, and unitary evolution in quantum mechanics, on the other. Until recently it was generally believed that a resolution of the information paradox would require a solid understanding of quantum gravity, something we are still lacking. However, striking recent progress has shifted the panorama, strongly suggesting that only minimal input from quantum gravity — namely from holography — seems to be needed. Once this is taken into account, semiclassical predictions can be reconciled with unitarity during black hole evaporation. I will overview the amazing progress achieved. This involves many ideas developed only recently, starting with holographic black holes and their evaporation, and ending with the island rule for the computation of entanglement entropy, and its derivation using replica wormholes.